Pendampingan Program Phbs Bagi Anggota Pmr Mula Di Sdn Sukabumi 2 Probolinggo - Ani Anjarwati; Ryzca Siti Qomariyah; Putri Fatimattus Az Zahra; Dita Refani Putri; Adenita Faradilla (LPPM Universitas Dharma Andalas, 2022)
Clean and Healthy Living Behavior or PHBS is a conscious application of behavior as a result of learning to enable individuals to provide help to themselves and the surrounding community in the health sector. One of the efforts implement PHBS is to wash hands before and after doing activities. The socialization was carried out at Sukabumi 2 Elementary School with the subjects of grade IV and V students to promote PHBS as an effort to prevent disease. Activities are carried out in elementary schools because at this level it is considered necessary to understand more deeply about their lifestyle. In the implementation of socialization using the